Hubungan Insomnia terhadap Kejadian Migrain pada Remaja - faridah aini; Raharjo Apriatmoko (Universitas Ngudi Waluyo, 2020)
Insomnia in the form of reduced quantity and quality of sleep that can cause changes neurotransmitter. Serotonin levels affect REM sleep and therefore the disturbance in serotonin levels will cause migraine. The purpose of this study was to determine the realationship of changes in sleep patterns to the incidence of migraine in teenagers. This research design was descriptive correlational with cross sectional approach. The population of this research was teenagers in Candi Subdistrict of Bandungan, with samples of 120 people taken by purposive sampling technique. Data collection tool for concentration level variable used questionnaires of Study Group of Psychiatry Biology Jakarta - Disruption of sleep patterns Rating Scale (KSPBJ-IRS) and Migraine Screen Questionnaire (MS-Q). Data analysis used frequency distribution and chi square test. The results showed that most teenagers did not experience insomnia (63.3%), most of them did not experience migraine (68.3%). There was an association betwen insomnia and the incidence of migraine in teenagers, with p value of 0.0001 (α=0,05). Should teenagers control sleep patterns by making a schedule to prevent and control the incidence of migraine.